METODE: AT VÆKKE UNDERSØGELSESOBJEKTERNES GENSTRIDIGHED: Om gæringsprocesser i interviewanalyse - Knudsen, Fabinne (Tidsskriftet Antropologi, 2002)
To analyse and interpret qualitative data is like putting a puzzle together. In this article it is argued that the most valuable pieces often are those which do not fit into the developing pattern. They are the ones that force one to widen or reconsider one’s hypothesis, and thereby disclose new knowledge. In the first part of the article, this idea is illustrated by use of a report, based mainly on interviews, on incentives and barriers to comply with safety rules in Danish merchant ships. The analysis of the interviews revealed many inconsistencies and contradictions between the answers and even within the same interviews. This reflects ambivalence or contrasting feelings or signals (e.g. contradictory demands from shipowners and authorities or ambivalence toward the shipowner or the foreign crew members). The second part is initiated by setting out the strange feeling acquired in the course of the analysis, that at one time the author stopped mastering what was happening, as if the statements began to interfere independently of her own will. The author utilizes some of the works of Bruno Latour to understand this feeling. What she experienced, with Latour’s words, was a transition from objectivity to “objectory”. In other words the statements the author was trying to analyse began to “object” in an obstinate way. She learned from Latour that she’d better encourage them to do so, instead of trying to imitate an alleged disinterested objective research.